2003
DOI: 10.1136/bmj.327.7426.1251
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of treatment of unilateral visual impairment detected at preschool vision screening

Abstract: Objectives To test the efficacy of treatment for unilateral visual loss detected by preschool vision screening and the extent to which effectiveness varies with initial severity. Design Randomised controlled trial of full treatment with glasses and patching, if required, compared with glasses only or no treatment. Masked assessment of best corrected acuity after one year of follow up. Setting Eight UK eye departments. Participants 177 children aged 3-5 years with mild to moderate unilateral impairment of acuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 29 publications
5
128
0
4
Order By: Relevance
“…The current referral criterion used is VA of less than 6/9 in one or both eyes. A trial of treatment of unilateral visual impairment detected at pre-school vision screening 4 concluded that children with 6/9 or 6/12 vision in one eye (and normal vision in the other) benefited little from treatment. As testing on pre-school children is often less reliable than that on school-age children, it was felt that 6/9 is within the normal range of VA on a crowded test and therefore this referral criterion currently remains our standard.…”
Section: Discussionmentioning
confidence: 99%
“…The current referral criterion used is VA of less than 6/9 in one or both eyes. A trial of treatment of unilateral visual impairment detected at pre-school vision screening 4 concluded that children with 6/9 or 6/12 vision in one eye (and normal vision in the other) benefited little from treatment. As testing on pre-school children is often less reliable than that on school-age children, it was felt that 6/9 is within the normal range of VA on a crowded test and therefore this referral criterion currently remains our standard.…”
Section: Discussionmentioning
confidence: 99%
“…74,75,103 The visual acuity data in this study were obtained at the first visit, prior to any such period of spectacle wearing. Thus, many of the patients identified as having amblyopia in this study could potentially have been treated with spectacles alone and still had substantial improvement in acuity.…”
Section: Discussionmentioning
confidence: 99%
“…71 This may also explain why many patients who have anisometropic amblyopia respond simply to spectacles alone, [73][74][75] and why patients with anisometropic amblyopia are more likely to improve at later periods in life. 75 …”
Section: Findings In Animals With Experimentally Induced Anisometropimentioning
confidence: 99%
“…Screening and treatment at preschool age, when it is a sensitive period of visual development, lead to a better visual outcome. [8][9][10] However, screening for amblyopic children is labour-intensive, costly, and sometimes unreliable. [11][12][13][14] This situation is more evident in eastern Taiwan where a mixed population of mountain aborigines and Han Taiwanese people is scattered from mountains to coasts.…”
Section: Introductionmentioning
confidence: 99%